Analytical investigations on the lindane bioremediation capability of the demosponge Hymeniacidon perlevis. Issue 1 (15th January 2015) - Aresta, Antonella; Nonnis Marzano, Carlotta; Lopane, Chiara; Corriero, Giuseppe; Longo, Caterina; Zambonin, Carlo; Stabili, Loredana
Highlights: Lindane is a toxic pesticide still used without control in developing countries. We have studied the ability of the sponge Hymeniacidon perlevis to bioremediate lindane. Sponges are able to remove about 50% of lindane from seawater in 48 h. We also assessed the role exerted in lindane degradation by H . perlevis bacteria. The bacteria showed a remarkable removing capacity (97% of lindane removed in 8 days). Abstract: Lindane is an organochlorine pesticide that has been widely used to treat agricultural pests. It is of particular concern because of its toxicity, persistence and tendency to bioaccumulate in terrestrial and aquatic ecosystems. In this context, we investigated the ability of the demosponge Hymeniacidon perlevis to bioremediate lindane polluted seawater during in vitro experimentation. Lindane was extracted by solid-phase micro-extraction (SPME) and determined by gas chromatography–mass spectrometry (GC–MS). Furthermore, we assessed the role exerted in lindane degradation by bacteria isolated from the sponge. Sponges showed low mortality in experimental conditions (lindane concentration 1 μg/L) and were able to remove about 50% of the lindane content from seawater in 48 h. Bacteria isolated from sponges showed a remarkable remediating capacity (up to 97% of lindane removed after 8-days). A lindane metabolite was identified, 1, 3, 4, 5, 6-pentachloro-cyclohexene. The results obtained are a prelude to the development of future strategies for the in situ bioremediation of this pollutant.